Translation and Telefiction: Multimodal Analysis of Paratextual Pieces for HBO’s Looking - Villanueva-Jordán, Iván (2021)
This paper presents an analysis of the trailers for a telefiction series originally produced in English and simultaneously distributed in Spanish in Latin America. Looking (aired between 2014 and 2016 by HBO) was a contemporary dramedy series, a hybrid genre typical of the quality TV promoted by HBO, that told the story of three gay friends living in San Francisco. The aesthetics of the series reveals the auteur cinematic work of Andrew Haigh, a film director who applied his visual narrative repertoire to Looking. Using the multimodal analysis model proposed by Kaindl (2020) and the structure of communicative modes proposed by Chaume (2004) and Stöckl (2004), this paper analyzes the translation and Latin American adaptation of two trailers of the series to understand whether the semiotic integration of the paratexts represents or intensifies the narrative aspects of the hybrid genre series.